Ethnobotanical survey about the management of diabetes with medicinal plants used by diabetic patient in Region of Fez-Meknes, Morocco - Mechchate, Hamza; Es-safi, Imane; Jawhari, Fatima zahra; Bari, Amina; Grafov, Andriy; Bousta, Dalila (Ethnobotany Research and Applications, 2020)
Background: Diabetes mellitus is a major public health problem in Morocco with more than 1.6 million cases of diabetes in 2017 with an expectation to rise to over 2.7 million cases in 2045. The aim of this work is to provide ethnobotanical information on some of the medicinal plants used by diabetic patients to treat their illness in the region of Fez-Meknes (Morocco). Methods: A semi-structured and simple questionnaire was carried out. A total of 422 interviews were conducted with diabetic patients presented to diagnosis in the Hassan II Hospital center in Fez in Morocco. The data were analyzed through use value (UV) and relative frequency of citations (RFC). Results: In total, 50 plant species belonging to 27 families were reported. Lamiaceae (14%), Apiaceae (12%) and Fabaceae (12%) were reported as the most represented families. Among the collected species, 6 plants were reported for the first time as antidiabetic plants in Morocco. The most frequently cited plant species are Trigonella foenum graecum (8.41%), Olea europaea (7.71%) and Prunus amygdalus var. amara (7.71%). Almost 67% and 33% of diabetic patient use medicinal plants as a complement and alternatives to their medication respectively. Conclusion: This study showed the importance of medicinal plants in the healthcare system for treating diabetes. Knowledge of the use of medicinal plants that are used to manage diabetes may contribute to their preservation and to undertake further pharmacological studies. Keywords: Ethnobotanical survey, Diabetes, Management of Diabetes, Medicinal plant, Fez-Meknes, Morocco